2021
DOI: 10.3389/fpubh.2021.637484
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study on Formal and Informal Carers' Perceptions of Dementia Care Provision and Management in Malaysia

Abstract: Background: The number of people living with dementia worldwide is increasing, particularly in low- and middle-income countries (LMICs) where little is known about existing post-diagnostic care and support. This study aimed to better understand healthcare provision for people living with dementia in Malaysia, and to identify priorities for providing timely, quality, and accessible care and support to all.Methods: This is a qualitative interview study on care providers and facilitators (health and community car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…A more holistic approach to dementia education intervention via CPD activities in the form of training and courses can be conducted to improve the knowledge and attitudes towards dementia care, thus increasing the confidence in dementia management [ 44 ]. This training may also include updated information on the dementia care services available, with clear dementia management pathways to guide PCDs involved in coordinating care for people living with dementia [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…A more holistic approach to dementia education intervention via CPD activities in the form of training and courses can be conducted to improve the knowledge and attitudes towards dementia care, thus increasing the confidence in dementia management [ 44 ]. This training may also include updated information on the dementia care services available, with clear dementia management pathways to guide PCDs involved in coordinating care for people living with dementia [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“… 12 Additionally, informal care for PwD living at home is the only feasible option in resource-limited countries. 13 …”
Section: Introductionmentioning
confidence: 99%
“…They identified the main types of interventions available for informal caregivers of PwD, including psychoeducation and psychotherapy (eg, cognitive behavioural therapy), support groups, respite care, caregiver training (eg, occupational training) and mindfulness and exercise programmes. 13 However, previous studies have often reported a need for additional implementation studies that report strategies to ‘translate caregiver interventions into practice’ and ‘evaluate the mechanisms for sustainability within the healthcare system’. 19 20 Successful implementation also requires a comprehensive understanding of the barriers and facilitators to implementation and the contextual factors influencing dissemination of evidence-based practices.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, 60% of dementia cases reside in low-and middle-income countries [10]. In Malaysia, the prevalence of dementia is predicted to be 6.3, 12.6, and 45.4 million people in the years 2005, 2020, and 2050, respectively [11,12]. A nationwide survey of dementia reported that the prevalence is higher in individuals above 60 years old (8.5%), and in females especially, who did not receive formal education and live in rural areas [13].…”
Section: Introductionmentioning
confidence: 99%